Effects of Weight Loss and Aerobic Exercise Training on Adi-Pose Tissue Zinc α2-Glycoprotein and Associated Genes in Obesity - Shealinna X. Ge; Guoyan Li; Alice S. Ryan (Cells, 2023)
Zinc α2-glycoprotein (ZAG) has been implicated in fatty acid metabolism and utilization and is lower in obese and higher in cachexic adults compared to those of normal weight. Previous studies suggest that ZAG binds to the beta3-adrenergic receptor (β3AR) to influence fatty acid metabolism in adipose tissue by regulating hormone sensitive lipase (HSL). The purpose of this study is to investigate the effects of a six-month weight loss (WL) or aerobic exercise (AEX) intervention on adipose tissue and skeletal muscle ZAG mRNA levels and protein expression, as well as the expression of β3AR, and HSL. Abdominal adipose tissue (AB) and gluteal adipose tissue (Glut) and vastus lateralis muscle biopsies were performed before and after WL (n = 13) or AEX (n = 13). ZAG, HSL, and β3AR expressions were determined by RT-PCR, and ZAG and HSL plasma levels by ELISA. Body weight decreased by 9.69% (p < 0.001) in WL and did not change with AEX. Maximal oxygen consumption (VO2max) increased by 7.1% (p < 0.005) after WL and by 16.69% (p < 0.001) after AEX. WL significantly decreased body weight with a reduction of percentage of fat, fat mass, fat-free mass (FFM). AEX decreased percent fat and increased VO2max, but did not change fat mass and FFM. Abdominal ZAG and HSL mRNA levels did not change significantly after WL or AEX. There were no changes in plasma ZAG, HSL and adipose tissue β3AR mRNA levels after WL and AEX. ZAG, HSL and β3AR mRNA expressions in adipose tissue are positively associated each other. Adipose tissue abdominal and gluteal HSL are negatively associated with HOMA-IR (Homeostatic Model Assessment for Insulin Resistance), and both ZAG and HSL adipose tissue are negatively associated with fasting glucose and the glucose area under the curve. Further work is needed to elucidate the role of ZAG and HSL in the propensity for weight gain and the ability of exercise to mitigate these responses.